The Work of Postcolonial Game Studies in the Play of Culture - Murray, Soraya (Open Library of Humanities, 2018)
This article considers larger methodological questions of what political work is undertaken when scholars engage in postcolonial critiques of video games within academic intellectual frameworks. What is postcolonial game studies, and what is its purpose, within the context of larger issues of inclusion, representation, diversity, and the challenging of hegemonic power structures? After surveying some of the key literature in postcolonial game studies, the author provides critical frameworks for understanding the means by which these approaches have largely been excluded from video game studies, and their crucial function in operating against the grain of profit and innovation-driven discourses in games. This work is the extension of a larger discussion of inclusion, diversity, and tolerance discourse within the liberal academy, and particularly the functions of postcolonial, postmodern and other critical cultural scholarly interventions. In this article, the author argues for a postcolonial approach to game studies, but one that refuses to be reduced to an institutional cultural labor of due diligence, or according to Slavoj Žižek’s term, a ‘culturalization of politics’. Through the work of Stuart Hall and Sara Ahmed on intellectual diversity work within the context of large systems and academic institutions, this article asserts that the perception that critical theorizations (like postcolonial game studies) exert pressure on efficiency and innovation is greatly outweighed by the rich toolkits they bring to video games as maturing cultural forms.
Keywords: 1-Jeux vidéo; 2-Méthodologie de recherche décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé